A structure–function analysis of the yeast Elg1 protein reveals the importance of PCNA unloading in genome stability maintenance. Issue 6 (20th January 2017) - Shemesh, Keren; Sebesta, Marek; Pacesa, Martin; Sau, Soumitra; Bronstein, Alex; Parnas, Oren; Liefshitz, Batia; Venclovas, Česlovas; Krejci, Lumir; Kupiec, Martin
Abstract: The sliding clamp, PCNA, plays a central role in DNA replication and repair. In the moving replication fork, PCNA is present at the leading strand and at each of the Okazaki fragments that are formed on the lagging strand. PCNA enhances the processivity of the replicative polymerases and provides a landing platform for other proteins and enzymes. The loading of the clamp onto DNA is performed by the Replication Factor C (RFC) complex, whereas its unloading can be carried out by an RFC-like complex containing Elg1. Mutations in ELG1 lead to DNA damage sensitivity and genome instability. To characterize the role of Elg1 in maintaining genomic integrity, we used homology modeling to generate a number of site-specific mutations in ELG1 that exhibit different PCNA unloading capabilities. We show that the sensitivity to DNA damaging agents and hyper-recombination of these alleles correlate with their ability to unload PCNA from the chromatin. Our results indicate that retention of modified and unmodified PCNA on the chromatin causes genomic instability. We also show, using purified proteins, that the Elg1 complex inhibits DNA synthesis by unloading SUMOylated PCNA from the DNA. Additionally, we find that mutations in ELG1 suppress the sensitivity of rad5 Δ mutants to DNA damage by allowing trans-lesion synthesis to take place. Taken together, the data indicate that the Elg1–RLC complex plays an important role in the maintenance of genomic stability by unloading PCNA from the chromatin.